WASTE-FREE TECHNOLOGY FOR ENRICHMENT OF PURIFIC COPPER-ZINC ORE (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
As is known, copper-zinc ores are the most difficult for selective flotation. Difficulties areassociated with the nature of zinc blende and changes in its floatability under the influence ofprocesses occurring at the deposit, during grinding and during flotation.